First Clinical Experience With Single-Port Robotic Transanal Minimally Invasive Surgery: Phase II Trial of the Initial 26 Cases. Issue 8 (August 2021) - Marks, John H; Kunkel, Emily; Salem, Jean F.; Martin, Charles T.; Anderson, Brigitte; Agarwal, Samir
Abstract : BACKGROUND: Many transanal platforms have been developed to address the challenge of reach and vision when operating transanally. The single-port robot was specifically designed for narrow-aperture surgery and is a promising platform for minimally invasive transanal surgery. OBJECTIVE: The purpose of this phase II trial is to evaluate the safety and feasibility of the initial clinical experience with single-port robot transanal minimally invasive surgery. DESIGN: In a prospective phase II trial, patients with rectal neoplasms eligible for local excision were enrolled for single-port robotic transanal minimally invasive surgery. SETTING: The study was conducted between October 2018 and March 2020 at a tertiary referral hospital. PATIENTS/INTERVENTION: Twenty-six consecutive patients underwent single-port robotic transanal minimally invasive surgery resection of rectal lesions. MAIN OUTCOME MEASURES: The primary end point of the study was the efficacy and safety of single-port robotic transanal minimally invasive surgery. RESULTS: There were 13 men and 13 women, with an average lesion size of 2.9 cm (range, 1.0–6.0 cm) and average level of 4.8 cm from the anorectal ring (range, 0–30 cm). Ten patients had a preoperative diagnosis of adenocarcinoma, 7 of whom received neoadjuvant chemoradiation (range, 4500–5580 cGy with concurrent oral capecitabine). Eighty-eight percent of cases were completed by single-port robotic transanal minimally invasive surgery; 2 were converted to transanal endoscopic microsurgery, and 1 patient underwent a low anterior resection. There were no piecemeal extractions, and all margins were negative on final pathology. There were no mortalities, and the morbidity rate was 15.4%. There have been no local recurrences, with a mean follow-up of 5.8 months (range, 0–15.9 months). LIMITATIONS: The study was limited by small sample size, short-term follow up, and a single-surgeon experience. CONCLUSION: Single-port robotic transanal minimally invasive surgery procedures are safe and feasible in patients with select benign and malignant rectal lesions. Future trials will need to evaluate the long-term safety and efficacy of single-port robotic transanal minimally invasive surgery. See Video Abstract at http://links.lww.com/DCR/B605 . PRIMERA EXPERIENCIA CLÍNICA CON CIRUGÍA MÍNIMAMENTE INVASIVA TRANSANAL ROBÓTICA DE PUERTO ÚNICO: ENSAYO DE FASE II DE LOS 26 CASOS INICIALES: ANTECEDENTES: Se han desarrollado muchas plataformas transanales para abordar el desafío del alcance y la visión cuando se opera de manera transanal. El robot de un solo puerto fue diseñado específicamente para la cirugía de apertura estrecha y es una plataforma prometedora para la cirugía transanal mínimamente invasiva. OBJETIVO: El propósito de este ensayo de fase II es evaluar la seguridad y viabilidad de la experiencia clínica inicial con la cirugía mínimamente invasiva transanal con robot de puerto único. DISEÑO: En un ensayo prospectivo de fase II, los pacientes con neoplasias rectales elegibles para la escisión local se inscribieron para la cirugía mínimamente invasiva transanal robótica de puerto único. AJUSTE: El estudio se realizó entre octubre de 2018 y marzo de 2020 en un hospital de referencia terciario. PACIENTES / INTERVENCIÓN: Veintiséis pacientes consecutivos fueron sometidos a cirugía mínimamente invasiva transanal robótica de puerto único para resección de lesiones rectales. PRINCIPALES MEDIDAS DE RESULTADO: El criterio de valoración principal del estudio fue la eficacia y seguridad de la cirugía mínimamente invasiva transanal robótica de puerto único. RESULTADOS: Hubo 13 hombres y 13 mujeres, con un tamaño de lesión promedio de 2.9 cm (rango 1.0-6.0 cm) y un nivel promedio de 4.8 cm del anillo anorrectal (rango 0-30 cm). Diez pacientes tenían un diagnóstico preoperatorio de adenocarcinoma, 7 de los cuales recibieron quimiorradiación neoadyuvante (rango 4500-5580 cGy con capecitabina oral concurrente). El 88% de los casos se completaron mediante cirugía mínimamente invasiva transanal robótica de puerto único; 2 se convirtieron a microcirugía endoscópica transanal y 1 se sometió a una resección anterior baja. No hubo extracciones parciales y todos los márgenes fueron negativos en la patología final. No hubo mortalidad y una tasa de morbilidad del 15, 4%. No ha habido recidivas locales, con un seguimiento medio de 5, 8 meses (rango 0-15, 9 meses). LIMITACIONES: El estudio estuvo limitado por un tamaño de muestra pequeño, un seguimiento a corto plazo y la experiencia de un solo cirujano. CONCLUSIÓN: Los procedimientos de cirugía mínimamente invasiva transanal robótica de puerto único son seguros y factibles en pacientes con lesiones rectales benignas y malignas seleccionadas. Los ensayos futuros deberán evaluar la seguridad y eficacia a largo plazo de la cirugía mínimamente invasiva transanal robótica de puerto único. Consulte Video Resumen en http://links.lww.com/DCR/B605 . (Traducción—Dr. Eduardo Londoño-Schimmer )